The Effect of Digital Services and Sharia Financial Knowledge on Customer Decisions to Use Islamic Banking Products (Study on Generation Z in Watampone) - Haslindah S; Muhammad Yamin; Fitriani (Penerbit Jurnal Indonesia, 2025)
This study aims to analyze the effect of digital services, Islamic financial knowledge, and the effect of both simultaneously on Generation Z customers' decisions to use Islamic banking products in Watampone. The background of this research is based on the increasing digitization of financial services and the importance of Islamic financial literacy in supporting financial decisions according to sharia principles. This research uses a quantitative approach with survey method and purposive sampling technique, involving 100 respondents from Generation Z who are Islamic banking customers. Data analysis was conducted using multiple linear regression. The results showed that digital services had no significant effect on customer decisions, while Islamic financial knowledge had a significant effect. Simultaneously, digital services and Islamic financial knowledge have a significant effect on customer decisions. These findings confirm the importance of increasing Islamic financial literacy and the need to optimize digital services in Islamic banking targeting Generation Z.